Building Ecoliteracy Through Adiwiyata Program (Study at Adiwiyata School in Banda Aceh) - Mirza Desfandi; Enok Maryani; Disman Disman (Indonesian Journal of Geography, 2017)
This study is back grounded by importance of ecoliteracy for each individual. One of comprehensive efforts to build ecoliteracy in community is through Adiwiyata Program. This study is aimed to find out how the effectiveness of Adiwiyata Program in the effort to build students’ ecoliteracy in Banda Aceh. The method which is used is survey. The study is conducted in ten schools, with respondents are principal, teachers, administrative staff and students. Data analysis is done descriptively toward five variable and hypothesis test use nonparametric statistic test. The result of study showed that there is significant influence of school policy, curriculum implementation, school culture and school infrastructure management toward students’ ecoliteracy. The findings of study is the more effective four components of Adiwiyata is implemented, the higher of students’ecoliteracy. Therefore, four components of Adiwiyata should be implemented maximally, among other by strengthening Adiwiyata school team.